ANALISIS TRANSFORMASI DIRI KANISIAN MELALUI LATIHAN KEPEMIMPINAN IGNASIAN DI KOLESE KANISIUS JAKARTA - Alfred, Lambertus; Christiyanti, Maria Inggrit (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2024)
Ignatian leadership training programs at Kolese Kanisius Jakarta need to be evaluated periodically. The goal of this study is to examine how the Ignatian transformation designated as the goal of the leadership training programs is experienced by the students involved. This study also aims to clarify the characteristics of an Ignatian transformation and its prerequisites. The methods used in this research were a literature study mainly on Jesuit education and in-depth interviews with 9 former members of the Canisius College students council. All respondents were determined according to the purposive sampling principle while the data analysis was done using Miles and Huberman’s method. Ignatian transformation in this study is discussed in the sense of the formation of “men and women for and with others” and “human excellence,” which together form two complementary aspects of a single transformative process. This transformation takes place in Canisians who have completed their Ignatian leadership training at Kolese Kanisius. The transformative effect manifests in four areas of human excellence, namely the 4Cs (competence, conscience, commitment, compassion), aimed at service to others. Canisians display the qualities of Ignatian leaders who can reflect on themselves and direct their actions towards addressing the needs of the world. The self-transformation experienced by the Canisians results from leadership training aligned with the Ignatian Pedagogical Paradigm (IPP). Additional factors to this transformation include: a school environment that encourages ongoing formation, a shared Ignatian language within the school community, peer accompaniment throughout the formation process, and role models from the former Presidium.